ANALISA KEPUTUSAN PEMILIHAN JURUSAN PERHOTELAN AKPAR BSI YOGYAKARTA SEBAGAI PERGURUAN TINGGI DI KOTA PARIWISATA YOGYAKARTA - Diah Pradiatiningtyas (Universitas Bina Sarana Informatika, 2014)
Recently in year 2012-2013, hotel and hospitality industry in Yogyakarta growth rapidly. Yogyakarta is one of most wanted tourist destination in the world makes this industry growth fast. Hospitality business is a service business that puts service and built to maintain the same image therefore with high growth rate hotels in Yogyakarta then the competition in higher education institution especially Hospitality Studies Program will will also be more stringent. AKPAR BSI Yogyakarta in one of higher education institution which have hospitality program. AKPAR BSI Yogyakarta is one of element who responsible in creating qualify of human resources in hospitality industry. The aims of this research was to contribute in developing human resources in hospitality industry, so from the intention in choosing higher education, the industry can contribute how to maintain quality of higher education in hospitality industry. There are five independent: interest, future opportunities, internal motivation, campus attribute, and image; and one dependent variableis decision. 119 students from AKPAR BSI Yogyakarta become respondents in this research, data analyses with linear reggression. The results shown interest, internal motivation, campus attribute, and image affects decision the future opportunities don’t affect decision.